Economic Sustainability and Challenges of Micro and Small Enterprises in the One Town, One Product Program of the Department of Trade and Industry - Teresita Tawingan (International Journal of Entrepreneurship, Business, and Creative Economy, 2024)
This study examined economic sustainability in micro and small enterprises (MSEs) participating in the "One Town, One Product" (OTOP) program in Laguna Province. Using a descriptive correlation approach, the surveys gathered quantitative data from MSEs and Department of Trade and Industry (DTI) representatives. The aim of this study was to assess MSE economic performance, disparities between DTI and MSE views, challenge severity, and recommend improvements. Results showed that MSEs in OTOP Laguna achieved sustainability in financial performance, labor productivity, and product diversity. Disparities surfaced in areas such as human capital and goods quality. Challenges in product development were significant, whereas capacity building, standards compliance, market access, promotion, and finance were less concerning. An action plan was developed to boost financial performance, human capital, labor productivity, and community engagement, thus fostering a sustainable business environment for Laguna’s MSEs.